Gender parity in scientific authorship in a National Institute for Health Research Biomedical Research Centre: a bibliometric analysis. Issue 3 (23rd March 2021) - Shah, Syed Ghulam Sarwar; Dam, Rinita; Milano, Maria Julia; Edmunds, Laurel D; Henderson, Lorna R; Hartley, Catherine R; Coxall, Owen; Ovseiko, Pavel V; Buchan, Alastair M; Kiparoglou, Vasiliki
Abstract : Objective: Scientific authorship is a vital marker of achievement in academic careers and gender equity is a key performance metric in research. However, there is little understanding of gender equity in publications in biomedical research centres funded by the National Institute for Health Research (NIHR). This study assesses the gender parity in scientific authorship of biomedical research. Design: Descriptive, cross-sectional, retrospective bibliometric study. Setting: NIHR Oxford Biomedical Research Centre (BRC). Data: Data comprised 2409 publications that were either accepted or published between April 2012 and March 2017. The publications were classified as basic science studies, clinical studies (both trial and non-trial studies) and other studies (comments, editorials, systematic reviews, reviews, opinions, book chapters, meeting reports, guidelines and protocols). Main outcome measures: Gender of authors, defined as a binary variable comprising either male or female categories, in six authorship categories: first author, joint first authors, first corresponding author, joint corresponding authors, last author and joint last authors. Results: Publications comprised 39% clinical research (n=939), 27% basic research (n=643) and 34% other types of research (n=827). The proportion of female authors as first author (41%), first corresponding authors (34%) and last author (23%) was statistically significantly lower than male authors in these authorship categories (p<0.001). Of total joint first authors (n=458), joint corresponding authors (n=169) and joint last authors (n=229), female only authors comprised statistically significant (p<0.001) smaller proportions, that is, 15% (n=69), 29% (n=49) and 10% (n=23) respectively, compared with male only authors in these joint authorship categories. There was a statistically significant association between gender of the last author with gender of the first author (p<0.001), first corresponding author (p<0.001) and joint last author (p<0.001). The mean journal impact factor (JIF) was statistically significantly higher when the first corresponding author was male compared with female (Mean JIF: 10.00 vs 8.77, p=0.020); however, the JIF was not statistically different when there were male and female authors as first authors and last authors. Conclusions: Although the proportion of female authors is significantly lower than the proportion of male authors in all six categories of authorship analysed, the proportions of male and female last authors are comparable to their respective proportions as principal investigators in the BRC. These findings suggest positive trends and the NIHR Oxford BRC doing very well in gender parity in the senior (last) authorship category. Male corresponding authors are more likely to publish articles in prestigious journals with high impact factor while both male and female authors at first and last authorship positions publish articles in equally prestigious journals.